Fitness profile and mental toughness among policeman in Pasir Mas, Kelantan / Nur Fasihah Roni - Roni, Nur Fasihah (Faculty of Sport Science and Recreation, 2015)
This study described and compared the physical fitness profile and mental toughness among policeman in Pasir Mas, Kelantan. There were 100 subject aged 29.48±4.12 years old participated for this study in different gender which is consists 91 subjects of male and 9 of female. Cross sectional study design was used for this study. Descriptive statistic was used to describe physical fitness profile and mental toughness meanwhile Independent T-Test analysis to compare in different gender. Based on the results fitness test, subjects achieve a good fitness level on muscular endurance meanwhile very poor results on body composition. For the comparison, there is significance different (p<0.05) for handgrip and sit and reach test. There is not significant different (p>0.05) for the rest of physical fitness test. For mental toughness, there is not significant different (p>0.05) between male and female. Hence, all component is needed all subjects in order to dealing problem during carry out their duty.